Optimization of Surface Roughness Using Taguchi Methodology & Prediction of Tool Wear in Hard Turning Tools. (2015) - Sahu, Supriya; Choudhury, B.B.
Abstract: Coated tools are used to improve the performance in machining applications, such as high-speed machining and machining of hard materials. Surface roughness and tool wear prediction plays a significant role in machining for proper planning and control of machining parameters and optimization of cutting conditions. The present work studies the performance of multi-layer TiN coated tool in machining of hardened steel (AISI 4340 steel) under high speed turning, which has also been compared with that of uncoated tool. The influence of cutting parameters(speed, feed, and depth of cut)on surface roughness have been analyzed using Taguchi methodology. Finally, scanning electron microscopy (SEM) images are used to observe the surface morphology and to predict the tool wear. It has been found that the machining of hard materials at higher speeds and lower feeds is improved by using coated tools.